Self Efficacy sebagai Variabel Intervening dalam Mempengaruhi Servant Leadership terhadap Perilaku Kewarganegaraan Organisasi : Studi Pegawai Dinas Lingkungan Hidup Kabupaten Muaro Jambi - Amelinda Amelinda; Shofia Amin; Rts. Ratnawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine self-efficacy as an intervening variable in influencing the relationship between servant leadership and organizational citizenship behavior among employees of the Muaro Jambi District Environment Agency. The analysis method used is quantitative analysis. The population and sample consisted of 56 employees. Data collection was conducted by distributing questionnaires using a Likert scale. The statistical analysis used Structural Equation Modeling (SEM) techniques, with Partial Least Squares (PLS) as the tool for managing it using SmartPLS 4.1.1. The results of this study indicate that servant leadership has a positive and significant effect on organizational citizenship behavior, servant leadership has a positive and significant effect on self-efficacy, self-efficacy has a positive and significant effect on organizational citizenship behavior, and servant leadership has a positive and significant effect on organizational citizenship behavior and is mediated by self-efficacy.